Association between spinal disorders and different domains of physical activity among young adult men - Honkanen, Tuomas; Vaara, Jani P.; Pihlajamäki, Harri; Västilä, Ville; Kyröläinen, Heikki (Frontiers in Sports and Active Living, 2022)
Background There is limited evidence of how physical activity (PA) associates with low back pain (LBP) and neck pain (NP). Particularly, the association between occupational or commuting PA and LBP/NP is unclear. The aim of the present cross-sectional study was to investigate the association between spinal disorders and different physical activity domains in young and healthy adult men. Methods Self-reported leisure time, occupational and commuting PA, as well as LBP and NP, were studied using questionnaires among young Finnish males (n = 1,630). Logistic regression analysis was used to study the associations of PA domains, physical fitness, and spinal disorders. Regression models were adjusted for age, education, smoking, waist circumference, and the other PA domains. Results There was a positive association between moderate leisure-time PA and both LBP (OR: 1.51, 95% CI: 1.18–1.95) and NP (OR: 1.29, 95% CI: 1.00–1.66) compared to low PA. Furthermore, moderate (OR: 1.31, 95% CI: 1.00–1.71) and high (OR: 1.53, 95% CI: 1.15–2.02) leisure time PA groups had a higher likelihood of lumbago. Moderate (OR: 0.67, 95% CI: 0.51–0.90) and high (OR: 0.68, 95% CI: 0.48–0.95) occupational PA groups had lower likelihood for radiating LBP, while high occupational PA (OR: 0.72, 95% CI: 0.52–0.99) had lower likelihood for lumbago. Conclusions The associations between physical activity and LBP or NP seem to vary between different domains of physical activity among young healthy men. Commuting and occupation-related PA appear not to be harmfully associated with LPB or NP, whereas moderate-level leisure time PA may be associated with increased LBP and NP, and the respective high level may be associated with an increase in the prevalence of lumbago.